2023
DOI: 10.1002/jbt.23351
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of hispolon and its derivatives against apoptosis in cortical neurons induced by electromagnetic radiation from 4G mobile phone

Abstract: Electromagnetic radiation (EMR) from wireless devices, particularly mobile phones, is a potentially growing public health concern. In this study, the neuronal effects of EMR on primary cortical neurons (PCNs) from neonatal rat cerebral cortex and the protective role of hispolon (HIS) and its derivatives were investigated as a measure of cranial exposure during mobile phone use. PCNs were isolated and cultured from day-old neonatal rats, then exposed for 2 h to EMR emitted by a mobile phone operating at a frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Using the screening criterion of OB ≥ 5% and DL ≥ 0.14%, a total of 79 metabolites were identified as the key active metabolites. Two well-known styrylpyrone-class compounds, namely, hispolon and hispidin, have been widely isolated and verified to possess significant biological properties in Sanghuangporus species ( Gonindard et al, 1997 ; Anouar et al, 2014 ; Wu et al, 2014 ; Benarous et al, 2021 ; Liao et al, 2021 ; Palkina et al, 2021 ; Saka et al, 2023 ). However, these two compounds have not been included in the TCMSP database.…”
Section: Resultsmentioning
confidence: 99%
“…Using the screening criterion of OB ≥ 5% and DL ≥ 0.14%, a total of 79 metabolites were identified as the key active metabolites. Two well-known styrylpyrone-class compounds, namely, hispolon and hispidin, have been widely isolated and verified to possess significant biological properties in Sanghuangporus species ( Gonindard et al, 1997 ; Anouar et al, 2014 ; Wu et al, 2014 ; Benarous et al, 2021 ; Liao et al, 2021 ; Palkina et al, 2021 ; Saka et al, 2023 ). However, these two compounds have not been included in the TCMSP database.…”
Section: Resultsmentioning
confidence: 99%
“…It is distributed in China, Korea, Japan, Germany, Russia, Canada and other countries. Recent international medical studies reported that its pharmacological activities include anti-tumor, anti-oxidation, anti-inflammatory, liver protection, bacteriostasis, anti-virus, hypolipidemic and immune enhancement (Awadh et al, 2003;Benarous et al, 2015;Gründemann et al, 2016;Angelini et al, 2019;Liu et al, 2019;Yang et al, 2020;Li and Bao, 2022a;Zhang et al, 2022a;Machado-Carvalho et al, 2023;Saka et al, 2023;Tang et al, 2023). I. hispidus has an excellent development space as medical and functional food in future.…”
Section: Metabonomic Analysis Of Different Color Strainsmentioning
confidence: 99%
“…It is distributed in China, Korea, Japan, Germany, Russia, Canada and other countries. Recent international medical studies reported that its pharmacological activities include anti-tumor, anti-oxidation, anti-inflammatory, liver protection, bacteriostasis, anti-virus, hypolipidemic and immune enhancement ( Awadh et al, 2003 ; Benarous et al, 2015 ; Gründemann et al, 2016 ; Angelini et al, 2019 ; Li et al, 2019 ; Liu et al, 2019 ; Yang et al, 2019 ; Yang et al, 2020 ; Li and Bao, 2022a ; Zhang et al, 2022a ; Yang et al, 2022 ; Machado-Carvalho et al, 2023 ; Saka et al, 2023 ; Tang et al, 2023 ). I. hispidus has an excellent development space as medical and functional food in future.…”
Section: Introductionmentioning
confidence: 99%